1999
DOI: 10.1007/s004250050496
|View full text |Cite
|
Sign up to set email alerts
|

No Induction of ?-oxidation in leaves of Arabidopsis that over-produce lauric acid

Abstract: Leaves from transgenic Brassica napus L. plants engineered to produce lauric acid show increased levels of enzyme activities of the pathways associated with fatty acid catabolism (V.A. Eccleston and J.B. Ohlrogge, 1998, Plant Cell 10: 613-621). In order to determine if the increases in enzyme activity are mirrored by increases in the expression of genes encoding enzymes of beta-oxidation, which is the major pathway of fatty acid catabolism in plants, the medium-chain acyl-acyl carrier protein (ACP) thioesteras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 18 publications
2
20
0
Order By: Relevance
“…It can be concluded that medium-chain acyl-CoA oxidase activity exerts little control over the breakdown of storage lipid in germinating seeds. Long-chain acyl-CoA oxidase activity is about 8-fold less than that of medium-chain acyl-CoA oxidase in wild type seedlings (Table I) and leaves (26). If acyl-CoA oxidase plays a significant role in the control of peroxisomal ␤-oxidation (7,8), then long-chain acyl-CoA oxidase is likely to predominate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be concluded that medium-chain acyl-CoA oxidase activity exerts little control over the breakdown of storage lipid in germinating seeds. Long-chain acyl-CoA oxidase activity is about 8-fold less than that of medium-chain acyl-CoA oxidase in wild type seedlings (Table I) and leaves (26). If acyl-CoA oxidase plays a significant role in the control of peroxisomal ␤-oxidation (7,8), then long-chain acyl-CoA oxidase is likely to predominate.…”
Section: Discussionmentioning
confidence: 99%
“…In the majority of cases where crops have been genetically engineered to produce novel fatty acids, the accumulation of these products is much lower than that required for commercial exploitation (23,24). It is believed that in these plants the novel fatty acids are synthesized at significant rates but are subsequently degraded by peroxisomal ␤-oxidation (25,26). Moreover, Eccleston and Ohlrogge (25) provide evidence that in the case of plants producing medium-chain fatty acids, medium-chain acyl-CoA oxidase activity is up-regulated to facilitate this degradation.…”
mentioning
confidence: 99%
“…In the absence of a mechanism for transporting acetyl-CoA, a similar process could be responsible for the movement of carbon skeletons derived from ␤-oxidation of fatty acids out of the peroxisome. The fact that plant cells do respire lipids also is implied by the fact that the capacity for ␤-oxidation is present in many tissues that lack the glyoxylate cycle (16,33).…”
Section: Discussionmentioning
confidence: 99%
“…Because the rate of FA degradation was strongly enhanced in leaves of the tgd1-1 mutant ( Figure 9C; Fan et al, 2013a), we sought to determine the enzymatic activity of acyl-CoA oxidase (ACOX), which catalyzes the first and rate-limiting step in the b-oxidation cycle (Aoyama et al, 1994) and is a reliable indicator of peroxisomal b-oxidation capacity (Eccleston et al, 1996;Hooks et al, 1999). Compared with the wild type, there was no significant difference in ACOX activity with long-chain acyl-CoA as substrate in leaves of tgd1-1 (Supplemental Figure 9A).…”
Section: Disruption Of Sensitive To Freezing2 Affects Lipid Content Amentioning
confidence: 99%